Apakah indikasi kecurangan laporan keuangan perbankan dipengaruhi oleh keenam elemen fraud hexagon? - Komang Dandy Andriadi (Akuntansi dan Teknologi Informasi, 2025)
Purpose – This study aims to examine whether the indications of financial statement fraud in the banking sector are influenced by the six elements of the fraud hexagon. Methods – The sample was determined using a purposive sampling technique, resulting in 40 banking companies in Indonesia observed over a five-year period from 2019 to 2023. Data analysis was conducted using binary logistic regression, processed with STATA 17 software. Findings – The results indicate that the capability and opportunity elements have a positive influence on indications of financial statement fraud. In contrast, the stimulus, collusion, rationalization, and ego elements do not significantly influence indications of financial statement fraud. Implications – These findings contribute to the existing literature on the empirical examination of the fraud hexagon theory, which remains relatively novel. The results indicate the necessity for further empirical investigations to substantiate and validate the theory's applicability. Moreover, this study offers practical implications for financial regulatory authorities in Indonesia, particularly in formulating policies and regulations within the banking sector. Originality – The novelty of this study lies in examining the fraud hexagon theory within Indonesia’s banking sector from 2019 to 2023. This research provides new evaluative insights for regulators and practitioners to continuously enhance fraud prevention strategies.